Requirement for BDNF in the reconsolidation of fear extinction - Radiske, Andressa (2015)
Therapies based on the impairment of reconsolidation or the enhancement of extinction offer the possibility of decreasing the persistent recollection of distressing memories. However, the direct interplay between reconsolidation and extinction has rarely been considered. Previously, we reported that reactivation induces reconsolidation of fear extinction memory. Here, using a step-down inhibitory avoidance learning paradigm in rats, we show that intrahippocampus infusion of function-blocking anti-BDNF antibody immediately or 6 h after extinction memory reactivation impairs the reconsolidation of extinction. Extinction memory reactivation increases proBDNF, BDNF, and tropomyosin receptor kinase B (TrkB) phosphorylation levels in dorsal CA1, while blocking BDNF maturation in the hippocampus with plasminogen activator inhibitor 1 hinders the persistence of extinction and induces the recurrence of fear. Moreover, coinfusion of recombinant BDNF (0.25 μg/side) after extinction memory reactivation impedes the recovery of the avoidance response induced by inhibiting gene expression and protein synthesis in the dorsal hippocampus. Our findings unravel a new role for BDNF, suggesting that this neurotrophin is necessary and sufficient to maintain the reactivated fear extinction engram.